Effect of Massage with Oil Balanced in Essential Fatty Acids on Development and Lipid Parameters in Very Premature Neonates: A Randomized, Controlled Study - Aurélie Garbi; Martine Armand; Any-Alejandra B; Catherine Sarté; Véronique Brévaut-Malaty; Barthélémy Tosello; Catherine Gire (MDPI AG, 2022)
Background: Oil massage versus only massage can increase preterm newborn development, especially weight gain, via a supposed percutaneous absorption of oil lipids, but data are contradictory. Aims: Investigating whether massage with a vegetable oil balanced in essential fatty acids improves neonatal weight gain, and digestive autonomy as proxy for neuro-development outcomes. Methods: A prospective monocentric randomized study was conducted in very premature newborns who received massage with oil (isio4 10 mL/kg/day, n = 18) versus with no oil (n = 18) for five consecutive days (10-min session twice daily) at a corrected gestational age of 34-35 weeks. Anthropometrics and clinical characteristics were recorded. Plasma triglyceride and total cholesterol concentrations were analyzed with an enzymatic kit. The fatty acid composition (weight%, mg/mL) of total plasma lipids and of red blood cell (RBC) membrane was analyzed by gas chromatography. Results: Weight gain velocity at the end of massage period was 12.3 ± 1.4 g/kg/day with oil vs. 9.8 ± 1.4 g/kg/day with no oil (p = 0.1). Digestive autonomy, plasma lipid parameters, polyunsaturated fatty acids in plasma total lipids or in RBC were comparable. The no oil group displayed a higher RBC level in nervonic acid at discharge (4.3 ± 0.2 vs. 3.4 ± 0.2%; p = 0.025) and in C18:1n-9 plasmalogen species at the end of the massage period and at discharge (0.73 ± 0.06 vs. 0.48 ± 0.06; 0.92 ± 0.06 vs. 0.69 ± 0.06%; p < 0.01), two molecules that are involved in neurodevelopment. Conclusions: The use of isio4 oil did not provide additional benefits for the development of very premature newborns, neither changed lipid metabolism nor polyunsaturated fatty acid biological status, which did not corroborate the existence of a percutaneous route for oil lipid absorption. The reason for different levels of nervonic acid and plasmalogen in RBC remains to be explored.